Associated dyslipidemia in patients with arterial hypertension treated at the Ambato Tamborapa-Bellavista health center, 2023 - Zurita Rodríguez, Lucy Ayde (2024)
The objective of this study was to establish the relationship between dyslipidemia and high blood pressure in patients treated at the Ambato Tamborapa Health Center - Bellavista, 2023. The methodology employed was a quantitative approach of basic, descriptive, prospective and correlational type was used with a non-experimental design. The sample consisted of 100 patients. Data analysis was conducted using the statistical software SPSS version 27 and Spearman's Rho correlation test was applied. The results indicate that 57% have mild systolic pressure, 32% moderate and 11% severe. While, in Diastolic Pressure 52% have a mild level, 44% have a moderate level and 4% have a severe level. In cholesterol, 61% have high levels and 39% have very high levels, HDL 46% have high levels and 54% have very high levels, LDL 90% have high levels and 10% have very high levels, triglycerides 79% have high levels and 21% have very high levels. Cholesterol, triglycerides and arterial hypertension obtained a positive and direct relationship, with cholesterol (r=0.165) for triglycerides (r=0.110) in HDL and LDL with arterial hypertension presenting a significance value p ≤ 0.05.